The Seasonal Occurrence of the Snoutbeetle, Phlyctinus callosus Boheman ( Coleoptera: Curculionidae) on Vines in the Robertson Area - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Snoutbeetles have been known as a pest in vineyards for many years (Whitehead, 1961a). Five species have been identified as economically important. As a rule only one, two or tliree of the species are to be found in the same area. A similar type of damage is caused by the various species of snoutbeetles but differences in the seasonal occurrence are important as regards the critical time for the application of chemical control measures. This information is available for four of the wine producing areas of the Western Cape, one of the exceptions being Robertson (Whitehead, 1961a; 196lb).